Femoral Osteonecrosis after Medial Femoral Condyle Bone Graft Harvest - Boretto, Jorge G. (Plast Reconstr Surg Glob Open, 2018)
The medial femoral condyle vascularized graft has become a useful resource in reconstructive microsurgery due to the rate of bony union, and the low rate of complication. We report osteonecrosis of the medial femoral condyle in a 65-year-old woman after harvesting a corticocancellous medial femoral condyle graft to treat a tarsometatarsal nonunion. We were not able to define whether a vascular or mechanical disorder could be the ultimate cause. However, because of the severity of the complication, we suggest informing patients who will undergo a medial femoral condyle flap about this infrequent complication.